2011
DOI: 10.1007/s12011-011-9106-x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Is More Toxic on Volume Bone Mineral Density than Tissue Bone Mineral Density

Abstract: It has been showed that Cd induces low areal bone mineral density, but we do not know the effect of Cd on cubic bone density. This study was aimed to investigate the effects of Cd on volumetric bone mineral density (VBMD) and tissue bone mineral density (TBMD) in male rats. Twenty-four Sprague-Dawley male rats were randomly divided into four groups that were given cadmium chloride by subcutaneous injection at doses of 0, 0.1, 0.5, and 1.5 mg/kg body weight for 8 weeks, respectively. Then, microcomputed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
5
0
2
Order By: Relevance
“…Recent research has focused on the putative roles that cadmium plays in volumetric BMD and bone morphometry. In vivo studies of Sprague-Dawley male rats have shown that cadmium exposure can induce low vBMD [49] by decreasing the trabecular number, thereby reducing the quantity of mineralized bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on the putative roles that cadmium plays in volumetric BMD and bone morphometry. In vivo studies of Sprague-Dawley male rats have shown that cadmium exposure can induce low vBMD [49] by decreasing the trabecular number, thereby reducing the quantity of mineralized bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of low-level cadmium exposure on bones, likely exerted via elevated bone resorption, has seemed to be enhanced after menopause [ 15 ], and this was confirmed by our observations, as we did not detect any association between the evaluated parameters and dietary cadmium exposure in our sample of premenopausal women. The current in vivo experiment has established that cadmium exposure induced low vBMD and had no impact on tissue BMD [ 18 ]; therefore, further attention should be paid to the influence of cadmium on bone microarchitecture.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity and the resulting threat to human health of any contaminant depends on the concentration; it is well known that sustained exposure to cadmium, lead and mercury at relatively low levels has negative effects [ 10 , 11 ]. Cadmium ranks seventh in the Agency for Toxic Substances and Disease Registry (ATSDR) list of elements posing the most significant potential threat to human health in the environment [ 12 ], and both human and in vivo studies have demonstrated cadmium to have toxic effects on bones, resulting in low bone mass, higher risk of osteoporosis and bone fractures [ 13 , 14 , 15 , 16 , 17 , 18 ]. Several population-based studies from Belgium, Sweden, Japan, and China have demonstrated an association between decreased bone mineral density and low-level cadmium exposure [ 15 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…O osso é um órgão alvo importante para a toxicidade do Cd. Tem sido demonstrado que a exposição ao Cd pode resultar em uma baixa massa óssea e um elevado risco de osteoporose e fraturas ósseas em animais experimentais e seres humanos (Chen et al, 2011a). Os osteoclastos são células responsáveis por realizar reabsorções ósseas.…”
Section: Análiseunclassified
“…O efeito negativo do Cd é conhecido há anos, mas somente estudos recentes, mostram que a baixa exposição crônica a este metal pode causar lesões renais e conduz a danos ósseos/alterações ósseas como efeito secundário. Essas alterações ósseas caracterizam-se por diminuição da massa óssea, osteoporose podendo levar a fraturas ósseas (Brzóska et al, 2005;Chen et al, 2009;Chen et al, 2011a…”
Section: Revisão De Literaturaunclassified